ANALISIS PENJUALAN DAN PERSAINGAN AIR MINERAL KEMASAN BOTOL SELAMA PANDEMI COVID-19 DI KOTA MEDAN MENGGUNAKAN RANTAI MARKOV ORDE DUA - Giawa, Freddy; Lubis, Riri Syafitri; Widyasari, Rina (Math Educa Journal, 2021)
Markov chain is a method used to identify variables in the present, which is based on past variables in order to obtain an estimate of the probability of these variables in the future. The CoVid-19 virus outbreak has also had a negative impact on economic problems, because this pandemic resulted in a decrease in sales of mineral water. in bottles that experienced a decline in sales results during the COVID-19 pandemic. The formulation of the problem of how companies compete during Covid-19 which continues to experience a decline in sales? . Based on the results of this study, there is a large chance of a second order transition, namely AQUA products in September, which is 61%, an increase of 0.39% from October, in October it was 61.39, a decline of 0.02% so that in November it was 61.37% while Le Mineral products in September were 39%, decreased 0.39% from October, October was 38.61%, experienced a fix in November so November was 38.61%.